Attitudes Toward Epilepsy Among Parents of Children With Epilepsy in Southern China - Yang, Haojun; Chi, Yunfang; Zhu, Ziqing; Huang, Kailing; Xiang, Lan; Xiao, Bo; Tang, Weiting; Feng, Li (Frontiers in Neurology, 2021)
Purpose: To evaluate the attitudes toward epilepsy among parents of children with epilepsy (CWE) in China and identify some related factors for future interventions for parents to offer more social support for CWE. Method: The Chinese Public Attitudes Toward Epilepsy (CPATE) scale was administered to 234 parents of CWE and 203 parents of normal children in Xiangya hospital during 2019-2020. Results: The cumulative score of the parents of CWE (26.427 ± 6.688) was significantly lower than that of the normal children group (32.330 ± 7.234, p < 0.001). Subanalysis showed more positive attitudes among parents of CWE than the control group (p < 0.001) towards education (4.765 ± 1.985 vs 6.621 ± 2.419), social life (6.556 ± 2.456 vs 8.010 ± 2.683), marriage (9.586 ± 2.675 vs 11.025 ± 2.900) and employment (3.876 ± 1.364 vs 4.5123 ± 1.283). The attitudes toward epilepsy among parents of CWE with seizures in public (27.16 ± 6.66) or during sleep (27.10 ± 6.38) were more negative than those without (25.35 ± 6.62 & 25.08 ± 7.10 respectively) (p < 0.05). In addition, female and low income were negatively related to parents’ attitudes toward epilepsy. Conclusions: More active policy guidance and adequate social supports should be given to parents of children with seizures in public or during sleep, to instruct their children to form a positive perception about epilepsy, which is expected to have a positive impact on their social abilities in the future.